DETERMINAN STRUKTUR MODAL DALAM PERSPEKTIF PECKING ORDER THEORY DAN AGENCY THEORY - Cahyani Nuswandari (Dinamika Akuntansi Keuangan dan Perbankan, 2013)
This study aims to analyze the factors that affect the capital structure. Factors examined as independent variables are profitability, company size, business risk, growth opportunities and managerial ownership. Variable profitability, company size, business risk is analyzed in the perspective of the pecking order theory and variable growth opportunities and managerial ownership is analyzed in the perspective of agency theory.Hypothesis testing using multiple regression. The population in this study is manufacturing companies listed in Indonesia Stock Exchange. Sampling technique using purposive sampling method. The samples used 222 observations are pooled data from 2008 to 2010. Types of data used are secondary data. Statistical tests showed hypotheses for the variables profitability and business risk accepted. This means that the profitability and business risk significantly and negatively related to capital structure. Hypothesis testing results for firm size variable positive and significant impact on capital structure. Thus the hypothesis is rejected due to size of company direction opposite hypothesis. Variable growth opportunities and managerial ownership and significant negative effect on capital structure.Keywords: capital structure, profitability, company size, business risk, growth opportunity, managerial ownership, the pecking order theory, agency theory.